The Prevalence of Bacterial Urinary Tract Infections Among School-age Children - Saad M. Hantoosh (Journal of Medical Genetics and Clinical Biology, 2024)
Urinary tract infections (UTIs) are the most common and serious bacterial infection in children. The current study aims at identifying the most prevalent symptoms and pathogenic bacteria linked to urinary tract infections in school-aged children in Al-Muthanna Province. Between October 2023 and April 2024, a urine samples were collected from 685 (417 female and 268 male) students across three age groups: 129 (19%) (6-12 years), 240 (35%) (>12-14 years), and 316 (46%) (>14-18 years) with symptoms of urinary tract infection. Female students (345) were significantly more affected by bacterial infections compared to male students (182), χ² (df=1, N=685) = 20.2, p < .001. In cases of UTI symptom onset, the likelihood of bacterial UTIs is 1.9 times higher for children aged >12-14 and 3.2 times higher for those aged >14-18 compared to children aged 6-12. The prevalence of symptomatic UTIs among schoolchildren increases with age, from 62% to 83.9% across different age groups. Among female students aged 6-18 with UTI symptoms, 82.7% had a bacterial UTI, compared to 67.9% of male students. Over 5% of schoolchildren without bacterial UTI exhibit moderate to marked pyuria. Hematuria percentages were comparable between individuals with and without bacterial UTIs. The average pH tended to be acidic for both groups, with infected individuals having a pH less than six and uninfected individuals having a pH less than seven. Escherichia coli was the predominant infectious followed by Enterococcus faecalis, Enterobacter aerogenes, Klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa at rates of 74%, 41%, 33%, 36%, 29% and 19%, respectively. Staphylococcus aureus and Staphylococcus epidermidis occurred at a frequency of 12% and 8%, respectively, while Streptococcus agalactiae occurred at a frequency of 3%.